2020
DOI: 10.1186/s12913-020-05195-5
|View full text |Cite
|
Sign up to set email alerts
|

Dispensations of benzodiazepines, z-hypnotics, and gabapentinoids to patients receiving opioid agonist therapy; a prospective cohort study in Norway from 2013 to 2017

Abstract: Background: Dispensations of benzodiazepines, z-hypnotics, and gabapentinoids to patients on opioid agonist therapy (OAT) are common and have pros and cons. The objectives of the current study are to define the dispensation rates of these potentially addictive drugs, and whether the number and the mean daily doses of dispensed OAT opioids and discontinuing OAT, are associated with being dispensed benzodiazepines, z-hypnotics and gabapentinoids among patients on OAT in Norway in the period 2013 to 2017. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…All gabapentinoids 503 (8) 463 (18) 509 (9) 497 (19) 582 (10) 507 (19) Pregabalin 348 (6) 330 (13) 359 (6) 331 (12) 413 7317 (12) Gabapentin 192 (3) 164 (6) 183 3203 (8) 207 4213 (8) Strong non-OAT opioids All strong non-OAT opioids 309 (5) 280 (11) 314 (6) 275 (10) 353 (6) 262 (10) Methadone tablets or injections* Weak non-OAT opioids All weak non-OAT opioids 768 (13) 169 (6) 675 (12) 150 (6) 674 (12) 137 (5) Codeine 562 (9) 125 (5) 500 (9) 107 4470 (8) 98 ( Open access documented abstinence from potentially addictive drugs at least 3 months prior to the initiation of CAS in OAT patients when indicated. 41 This may partly explain a lower dispensing rate of CAS in Norway compared with Swedish OAT patients.…”
Section: Gabapentinoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…All gabapentinoids 503 (8) 463 (18) 509 (9) 497 (19) 582 (10) 507 (19) Pregabalin 348 (6) 330 (13) 359 (6) 331 (12) 413 7317 (12) Gabapentin 192 (3) 164 (6) 183 3203 (8) 207 4213 (8) Strong non-OAT opioids All strong non-OAT opioids 309 (5) 280 (11) 314 (6) 275 (10) 353 (6) 262 (10) Methadone tablets or injections* Weak non-OAT opioids All weak non-OAT opioids 768 (13) 169 (6) 675 (12) 150 (6) 674 (12) 137 (5) Codeine 562 (9) 125 (5) 500 (9) 107 4470 (8) 98 ( Open access documented abstinence from potentially addictive drugs at least 3 months prior to the initiation of CAS in OAT patients when indicated. 41 This may partly explain a lower dispensing rate of CAS in Norway compared with Swedish OAT patients.…”
Section: Gabapentinoidsmentioning
confidence: 99%
“…Several studies indicate that around 50% of those patients who receive opioid agonist therapy (OAT) are dispensed benzodiazepines (e.g., diazepam and oxazepam), z-hypnotics (zolpidem and zopiclone), gabapentinoids (pregabalin and gabapentin), non-OAT opioids (e.g., morphine and oxycodone) or centrally acting stimulants (CAS) (e.g., methylphenidate and lisdexamphetamine) yearly [1][2][3][4][5] , notwithstanding the use of any potentially addictive illicit drugs. 1 6 7 Prescribing potentially addictive drugs to patients on OAT is controversial and comes with pros and cons.…”
Section: Introductionmentioning
confidence: 99%
“…Given the benzodiazepine-related harms in opioid-dependent patients, researchers have called for increased focus on the treatment of psychiatric co-occurring disorders in this condition to decrease the reasons for self-medication use of benzodiazepines [ 44 ]. Finally, dispensation of sedative-hypnotics, or benzodiazepines to patients in OMT are common and have pros and cons [ 53 ]. It has recently been shown that a substantial minority of OMT patients in Sweden were dispensed benzodiazepines (15%) and z-hypnotics (26%) [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Older SUD patients usually have more substance-related physical and mental comorbidities than younger patients, placing a higher responsibility on existing health care services. Previous observational studies have shown that receiving health services and being older were associated with more legal prescriptions for addictive medications compared with being younger, potentially making illegal substance use less likely [ 35 37 ]. This might explain the lower illegal substance use among older SUD patients.…”
Section: Discussionmentioning
confidence: 99%